The PULSE Program: A Life Skills Based Physical Activity Program for At-Risk Adolescents - Barker, Bryce (Université d'Ottawa / University of Ottawa, 2014)
The purpose of this doctoral thesis was to develop, implement and evaluate the PULSE program, a community-based physical activity and life skills program for at-risk youth. The thesis is composed of four articles. The first paper describes the rationale and development of the PULSE program which was designed to help youth develop the skills to self-regulate and successfully perform physical activity. The second article presents a process evaluation of the PULSE program. This article examines how the youth progressed through the program with regards to the five levels of the Teaching and Social Responsibility (TPSR) model, one of the frameworks on which the PULSE program is based. A second purpose of this study was to understand the youths’ perceptions of the impact of the program on these five levels. The results indicated that the program led to slight increases in the five levels of the TPSR model and the youth reported transferring the skills they learned related to the levels in their lives outside of the program. The third paper represents an outcome evaluation of the PULSE program. Results showed that youth who participated in PULSE increased their fitness, physical activity levels as well as a number of positive youth development outcomes. Finally, the fourth paper examined how the PULSE program helps support the tenets of Basic Needs Theory. The results indicated that the program successfully nurtured the three basic needs of autonomy, competence and relatedness. The overall findings suggest that the PULSE program is a practical, evidence-informed program that may help youth understand and apply life skills to be physically active as they approach adulthood, and also more generally in their lives. The current findings show promise for both Physical Activity (PA) and Positive Youth Development (PYD) outcomes but further research is needed to make causal links.
Keywords: Adolescent; Physical Activity; Positive Youth Development; Community; Program Evaluation